Direct Observation of Shock‐Induced Disordering of Enstatite Below the Melting Temperature. Issue 15 (3rd August 2020) - Hernandez, J.‐A.; Morard, G.; Guarguaglini, M.; Alonso‐Mori, R.; Benuzzi‐Mounaix, A.; Bolis, R.; Fiquet, G.; Galtier, E.; Gleason, A. E.; Glenzer, S.; Guyot, F.; Ko, B.; et al.
Abstract: We report in situ structural measurements of shock‐compressed single crystal orthoenstatite up to 337 ± 55 GPa on the Hugoniot, obtained by coupling ultrafast X‐ray diffraction to laser‐driven shock compression. Shock compression induces a disordering of the crystalline structure evidenced by the appearance of a diffuse X‐ray diffraction signal at nanosecond timescales at 80 ± 13 GPa on the Hugoniot, well below the equilibrium melting pressure (>170 GPa). The formation of bridgmanite and post‐perovskite have been indirectly reported in microsecond‐scale plate‐impact experiments. Therefore, we interpret the high‐pressure disordered state we observed at nanosecond scale as an intermediate structure from which bridgmanite and post‐perovskite crystallize at longer timescales. This evidence of a disordered structure of MgSiO3 on the Hugoniot indicates that the degree of polymerization of silicates is a key parameter to constrain the actual thermodynamics of shocks in natural environments. Plain Language Summary: The study of silicate materials at extreme pressures and temperatures provides insight on the evolution of planetary bodies evolution during solar system formation. During their accretion, rocky bodies have undergone several collisions and possibly planetary impacts that have transformed their minerals. The microscopic processes occurring during such events are not fully understood. In this study, we used high‐power lasers to generate shock waves into MgSiO3 enstatite crystals, creating conditions comparable to the deepest part of the early Earth mantle and large planetary impacts. During the shock wave transit, within few nanoseconds, we probed the structure of shocked enstatite between 14 ± 3 and 337 ± 55 GPa using intense X‐ray pulses from Linac Coherent Light Source X‐ray free electron laser facility. We found that, when shocked between 80 ± 13 GPa and the conditions of equilibrium melting (above 170 GPa), enstatite transforms into a disordered structure instead of forming bridgmanite or post‐perovskite—the expected equilibrium phases. This disordered structure is similar to MgSiO3 glass or liquid and is observed up to 337 ± 55 GPa. This study provides the first direct measurement of shocked enstatite structure and suggests that the observed disordered state is an intermediate phase on the transformation pathway of bridgmanite in natural impacts. Key Points: We performed ultrafast X‐ray diffraction of orthoenstatite crystals shock compressed up to 337 ± 55 GPa on the Hugoniot A disordered structure was observed from 80 ± 13 GPa along the Hugoniot, well below the melting temperature The degree of polymerization strongly influences the kinetics of recrystallization in shocked silicates